MEMAHAMI SUPERVISI PENDIDIKAN - faur, Ari Rahayu; Nurul Afifah Ainun; Halimatus Sa'diyah; Atik Nurul Khoiriyah (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
Education is essential to the progress of the nation, involving students, teachers and learning materials that are influenced by society and the environment. The government strives to produce a quality generation to compete nationally and internationally. Principals as supervisors play a crucial role in encouraging the growth of teachers' and students' potential, improving educational efficiency. The quality of education in Indonesia is declining due to rigid supervision, inadequate infrastructure, cheating in national exams, and KKN problems. Educators must work to improve this situation to improve the quality of education. This study uses qualitative research methodology to investigate and describe educational supervision in RA PIQ Sangatta Utara. To observe the research subject directly, the researcher will conduct a field study. The three data collection methods that will be used in this qualitative research are observation, documentation, and interviews upervisi education plays a crucial role in improving the quality of education. Through a supportive and guiding approach, supervision helps teachers to develop their teaching skills so as to create an effective learning environment. Its main goal is to improve the quality of teaching and learning and stimulate positive changes in the components that contribute to better education. With good coordination between all elements of education, such as teachers, students, curriculum and other resources, educational institutions can achieve higher standards, ensuring an engaging and effective learning process for all involved.